Controlador multi-ressonante para rejeição de perturbações com frequência variante no tempo em plataformas Stewart - Culau, Jonathan (2021)
This work presents the design of a robust disturbance rejection control scheme for Stewart platforms. To fully take into account the system nonlinearities, the quaternion based description is used along with a Quasi-Linear Parameter Varying representation. In order to provide robust output regulation, in the presence of frequency-varying disturbances, we propose the design of a multi-resonant internal model controller. The closed-loop stability is guaranteed by a state-feedback law synthesized via a convex optimization problem subject to linear matrix inequalities. The stability proof fully takes into account the platform nonlinearities and it is valid it is valid for a set of admissible initial conditions D. The numerical results obtained via simulations show the efectiveness of the multi-resonant controller applied to a Stewart platform in the case that the platform is used as a stabilization device on the ocean where the ocean waves generate frequency-varying harmonic disturbances.